SOCIAL MEDIA AND ENTREPRENEURSHIP DEVELOPMENT NEXUS IN BENUE STATE NIGERIA: EVIDENCE FROM A BINARY LOGISTIC REGRESSION MODEL - Agbor, Margaret Oka; Lifu, Dr. Frank Lifu; Osang, Joseph Eja-; Lifu, Odey Christopher (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study carried out an analysis of social media and entrepreneurship development nexus in Benue State. The researcher used mainly primary data from a sample of three hundred entrepreneurs in Zone A, B & C in Benue State Nigeria. The primary data was obtained using a structured questionnaire. The data collected were analyzed using logit regression to establish the relationship between social media and entrepreneurship development while principal component analysis was used to identify the most important factors that affects the use of social media in entrepreneurship development. The result of the binary logistic regression analysis indicates that Social Media added significantly to the model/prediction. This means that the logistic model was statistically significant at 5 percent level of significance. Increasing the use of social media was associated with an increased likelihood of entrepreneurship development in Benue State. The logistic regression model was statistically significant, using values from the Omnibus Test of Model Coefficient. The model explained of the variance in post harvest losses of orange in the studied areas and correctly classified of cases. Use of social media was 0.018 times more likely to bring about entrepreneurship development in the studied areas. It was concluded that social media have a positive and significant effect on entrepreneurship development in Benue State Nigeria. It was recommended among others that entrepreneurs in the study area should engage more qualified personnel who can create the right content needed to engage the diverse customers of the business. When this is done, the likelihood of the use of social media in bringing about entrepreneurship development in Benue State can be increased.